2020
DOI: 10.1111/nin.12341
|View full text |Cite
|
Sign up to set email alerts
|

Parental experience of hope in pediatric palliative care: Critical reflections on an exemplar of parents of a child with trisomy 18

Abstract: The purpose of this study is to analyze the experience of hope that appears in a parent's blog presenting everyday life while caring for a child with Trisomy 18 (Edwards syndrome). The author, Rebekah Peterson, began her blog on 17 March 2011 and continues to post information on her son Aaron's care. The analysis of hope in the blog is carried out using a mixed methodology: initial and focused coding using Charmaz's constructed grounded theory and elements of Colaizzi's method. Each aspect of hope is coded thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Corroborating our results, hope is considered by parents of children and adolescents with chronic diseases as the first and last strategy for dealing with moments of crisis ( 30 ) . We highlighted that types of hope act as waves of family hope, changing in the face of different factors and unique family experiences.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Corroborating our results, hope is considered by parents of children and adolescents with chronic diseases as the first and last strategy for dealing with moments of crisis ( 30 ) . We highlighted that types of hope act as waves of family hope, changing in the face of different factors and unique family experiences.…”
Section: Discussionsupporting
confidence: 57%
“…The feeling of uncertainty is usually present in the families of children and adolescents living with chronic illness. A study developed with parents in the context of pediatric palliative care showed that their experience of hope was based on uncertainty ( 30 ) . The uncertainty was related to the concern about the worsening of the child’s health, and his death, leading to an abrupt loss of hope ( 30 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another metaphorical description attempting to grasp the fluctuation of the care process is the notion of living “filled with ups and downs” (Rallison and Raffin-Bouchal 2013 , p. 197). This latter metaphor and the similarly expressed “roller coaster ride” appear quite often in studies on parental hope and their experience of caring for their seriously ill children (Bally et al 2018 , p. 92, Szabat 2020 , p. 5). Moreover, near-death and grieving experiences are described as “being in the in-between” (Rallison and Raffin-Bouchal 2013 , p. 197), signalling the uncertainty of daily life as well as the permanent duality of being near death, which families must cope with every day.…”
Section: The Dynamic Aspect Of Hope In Marcel’s Phenomenology and End-of-life Studiesmentioning
confidence: 99%
“…The seeming paradox of hoping for a cure of an incurable cancer did not interfere with the process of ACP Rempel et al ( 2012 ) (Canada) Glaser’s grounded theory and ChCGT ‘Parenting under Pressure’ process consists of 4 phases: (1) realizing and adjusting to the inconceivable; (2) growing increasingly attached; (3) watching for and accommodating the unexpected; (4) encountering new challenges Roscigno et al ( 2012 ) (USA) Semi-structured interviews, data came from a longitudinal multiple case study investigation Parents relied on hope as an emotional motivator, whereas most HPs described parents’ notions of hope as out of touch with reality. Parents perceived that such divergent beliefs about the role of hope negatively shaped communicative interactions and reduced trust with some of their providers Szabat ( 2020 ) (Poland) Initial and focused coding using ChCGT and elements of CoDPh The experience of PH consists 3 aspects: hope for the longest possible presence of a child with a family, hope for control over situations, pain, and symptoms, and existential facets of hope Timmermann et al ( 2015 ) (Denmark) A phenomenological-hermeneutic study based on Paul Ricoeur’s hermeneutic The findings reveal an influence of nature/weather on patients’ behavior. The analysis revealed 3 themes: (1) the experience of inner peace and an escape from negative thoughts; (2) the experience of a positive mood; (3) hope and the experience of good memories Vachon et al ( 2009 ) (Canada) A conceptual analysis 11 dimensions for the concept of EOL spirituality: (1) meaning and purpose in life; (2) self-transcendence; (3) transcendence with a higher being; (4) feelings of communion and mutuality; (5) beliefs and faith; (6) hope; (7) attitude toward death; (8) appreciation of life; (9) reflection upon fundamental values; (10) the developmental nature of spirituality; (11) its conscious aspect …”
Section: Introductionmentioning
confidence: 99%